1994
DOI: 10.1007/bf02221451
|View full text |Cite
|
Sign up to set email alerts
|

A lumbar chordoma treated with a wide resection

Abstract: Chordomas are rare skeletal tumors arising from the embryonic remains of the notochord [18, 30]. These tumors tend to appear in midline regions, particularly at the upper and lower extremities of the spinal column. We report the case of a 74-year-old woman with radicular compression associated with an L3 chordoma that was treated with a wide resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…A great amount of clinical data can be found in the literature supporting en bloc resection as the only treatment associated with long disease-free survival for chordomas [3,4,10,18,19,20,31]. Treatment of recurrences and intralesional excision cannot prevent local tumor recurrence even if survival can be quite long (with asymptomatic or, more frequently, symptomatic growing tumor).…”
Section: Introductionmentioning
confidence: 99%
“…A great amount of clinical data can be found in the literature supporting en bloc resection as the only treatment associated with long disease-free survival for chordomas [3,4,10,18,19,20,31]. Treatment of recurrences and intralesional excision cannot prevent local tumor recurrence even if survival can be quite long (with asymptomatic or, more frequently, symptomatic growing tumor).…”
Section: Introductionmentioning
confidence: 99%
“…2,[11][12][13][14][15] Efforts to perform en bloc resections are warranted, even in the cervical spine 16 if the sensitivity of this tumor to palliative techniques, such as radiation, is only partial or a matter of indecision in the long-term. [17][18][19] The size of these tumors at diagnosis is sometimes so large that it prevents oncologically adequate treatments.…”
mentioning
confidence: 99%
“…1,13,18,27,29,32 Resection with tumor-free margins has already been validated for effectiveness in both local control and longterm prognosis for chordomas arising from the thoracic, lumbar, or sacral spine. 3,4,9,19,23,27,33 Hence, the ideal aim of en bloc cervical chordoma resecion is to achieve tumorfree margins, with wide margins being the goal for the pathology report and marginal margins being a nonideal but acceptable outcome. We found that, although marginal margins (attained in 56% of cases) were reported overall significantly more frequently than both wide (19%) and violated (25%) margins, this relationship was not conserved when the cases were stratified according to tumor location.…”
mentioning
confidence: 99%